Estimation and validation of wind speed by using spatial interpolation - Yap, Yee Von (2015)
The increasing of wind hazard damages in Malaysia shows that wind speed has played an important role in weather forecast. Interpolation method is vital when estimating wind speed especially for a location which do not has a weather forecast station. In this study, three methods of spatial interpolation which are Inverse Distance Weighting (IDW), Kriging and Spline were compared to determine their suitability for estimating wind speed. All the methods are evaluated by using standard error regression and correlation coefficient analysis. Based on the results obtained, it was shown that Kriging is more suitable when estimating wind speed for a study point within an enclosed area while IDW and Spline are more suitable for study point between two locations. Therefore, the suitability of different spatial interpolation method is varies for different arrangements of location. Future studies with more data collected, denser sample points and different cases can be carried out to obtain a more accurate result.